A Discourse of the Indigenous Peoples' Rights and Their Contributions to the Indonesian Development: Lessons Learned from New Zealand - Jamin, Mohamad; Hermawan, Sapto; Mulyanto, Mulyanto (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2023)
The struggles of indigenous peoples in both New Zealand and Indonesia to gain legal recognition remain ongoing. This study focuses on two central aspects. Firstly, it examines the historical-legal journey of indigenous peoples in their quest for legal acknowledgment. Secondly, it makes a comparative analysis with New Zealand, highlighting the potential contributions that indigenous peoples can provide to their respective countries. The study follows a legal research methodology, linking existing issues with authoritative sources and real-world situations. The findings reveal that in New Zealand, indigenous peoples possess a legal standing, albeit not entirely comprehensive. Conversely, Indonesian regulations do not provide strong legal support for indigenous people's rights. Despite their limited rights, indigenous peoples in New Zealand have made significant contributions to the nation's development. Additionally, the article contends that given their fundamental role in the founding of the Indonesian State, it is time for indigenous peoples to receive proper recognition for their substantial contributions to the nation's development.DOI: https://doi.org/10.22304/pjih.v10n3.a3